Economic theory and the construction industry - Hillebrandt, Patricia M. (London: Macmillan, Distributed in the U.S. by Halsted Press, New York, 1974)
The book deals with the economics of the construction industry, the market and the contracting firms. The demands on the industry are examined from a theoretical standpoint including an examination of the intricacies of the market for housing, the importance of the accelerator in derived demand and the peculiarities of social type demand9, e.g. hospitals and schools. The theory is related to the practice of forecasting demand for construction in all major sectors. The nature of the supply situation is analysed, keeping always in sight the problem of the relationship of the underlying cost and revenue functions to the requirement in the industry to determine cost and price separately for each individual project.
Includes bibliographical references: p. [215]-220 and index.
rpm 27/09/2017
Loans
Keywords: Construction industry; Technology & Engineering -- Construction -- General; Industries